State, Women and Democracy in Nigeria, 1999-2007 (2011)
Studies on the transition from dictatorship to democracy often argue that democracy provides a great opportunity for the advancement of women’s political participation. This is premised on the equal participatory opportunity that democracy offers to all adult citizens. However, the extent to which this is borne empirically is yet to be established. This study, therefore, examined the extent to which the Nigerian state, under President Obasanjo, enhanced women political participation. It explored the relationship between democracy and women political participation by investigating the factors that determine women’s representation in national government structures such as senior positions in the public sector and political parties. The study adopted a survey design supplemented with in-depth interviews and key informant interviews. Six hundred copies of a questionnaire, 100 per geo-political zone, were administered to four purposively selected samples of civil servants, politicians, academics, and parliamentarians. Twenty in-depth interviews were held, involving a Senior Special Assistant to the Minister of Education, parliamentarians, staff of the National Assembly, directors in the Federal Ministries of Women’s Affairs and Education, academics, politicians. Six key informant interviews were held with leaders of women organizations purposively selected across the six geo-political zones. Library and archival documents, including official government gazettes and reports were the main sources of secondary data. Descriptive statistics and content analysis were used to analyze the data. The number of women in elective and appointive offices increased from 10 percent in 1999 to 16.6 percent in 2003 and to 26.7 percent in 2007. The ratification of several international conventions on women’s rights had raised the awareness of women’s rights about productive resources like land and capital as part of fundamental rights. The level of awareness among men and women regarding existing gender gaps in access to power and political positions had become widespread. Majority of male respondents (87.2%) maintained that democracy improved women’s political participation, while 50.4% of female respondents believed women’s political participation was still weak. Factors affecting women participation were; persistent tradition of male dominance and obstacles placed by religion and culture on the path of women advancement and emancipation. Entrenched culture of political violence, the “winner takes all” electoral system, coupled with increased poverty and economic hardships took a heavier toll on women than men and had dire consequences for women’s capacity for political participation. Female representation in governance though increasing had been constrained by a culture of patriarchy, tense and violent character of political competition. The enlarged space for women participation in politics under democratic rule had not translated into active political participation for many of them. The limitations could be overcome over time with more advocacies by civil society groups, introduction of some form of proportional representation and a sustained programme of civil and political education for both men and women.